Government Actions And The Mineral Industry (The National Institute for Occupational Safety and Health (NIOSH), 1981)
Metals From Oil Shale. -A Geological Survey News Release in mid-January indicated that a surface sample analysis of oil shale in central Montana found a ton of shale to contain up to 13 pounds of zinc, 2 pounds of nickel, 1.8 pounds of molybdenum, 16 pounds of vanadium oxide, and nearly a quarter pound of selenium. It might be possible to recover some of these metals economically on a byproduct basis. The shale in central Montana was also estimated to contain 180 billion barrels of synthetic crude oil, which compares to estimated oil reserves in the Middle East of 360 billion barrels. Merchant Fleet Dwindles. -The National Maritime Council reports that although the U.S. is the world's largest trading power and that well over 90% of its foreign trade is conducted by shipping, the U.S. fleet is tenth in absolute numbers and less than 5% of its foreign trade is carried on U.S. ships. In 30 years, the U.S. fleet has dwindled from over 4,000 oceangoing vessels to about 600. U.S. ships carry less than 2% of imported iron ore, bauxite, and tungsten, and only 3% of oil imports.